Microwave energy output from a superconducting cylindrical resonator through an E-plane tee; Soviet Physics - Technical Physics; Vol. 32, № 6 - Avgustinovich V. A. Vladimir Andreevich (1987, 1987)
В фонде НТБ ТПУ отсутствует